Productivity of trap catches in different fishing ground at Lhok Kuala Daya, Aceh Jaya - Rizal, Muhammad; Hafinuddin, Hafinuddin; Fuadi, Afdhal; Khairi, Ikhsanul; Rahayu, Rosi; Al-misbah, Iyan (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
Trap fishing gear offers several advantages, including high selectivity, the ability to keep fish alive, and support for sustainable fisheries. The productivity of catches around coral reefs and fish aggregating devices (FADs) is important to study in order to evaluate fish diversity in deeper waters across biological, genetic, species, and ecological levels. Such assessments are crucial for environmental conservation and for management based on diversity and dominance indices. This study aimed to determine the productivity, diversity, and dominant species composition of trap catches in two fishing grounds (FGs): coral reef areas and FAD zones at Lhok Kuala Daya, Aceh Jaya. The research employed an experimental fishing method, conducting five fishing operations in each zone. The overall diversity index of trap catches in Lhok Kuala Daya was 1.26, indicating a moderate level of diversity. The diversity index for catches around coral reefs was 1.15, while around FADs it was 1.58. The overall dominance index value of trap catches was 2.74, with dominance values of 0.74 in coral reef areas and 2.00 in FAD zones. These results indicate a low level of species dominance and a moderately diverse fish community in both fishing zones.Keywords:ProductivityTrapcatchFishing groundKuala daya